1983
DOI: 10.2105/ajph.73.7.795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Active and Passive Surveillance System of Primary Care Providers for Hepatitis, Measles, Rubella, and Salmonellosis in Vermont

Abstract: Between June

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 11 publications
4
58
1
2
Order By: Relevance
“…This study has ascertained cases through the use of a well-established surveillance methodology shown to be more effective than other methods. 16,17 However, it is likely that there is some degree of underascertainment. Previous reports for studies ascertaining cases through the BOSU have indicated that ascertainment rates usually lie between 75 and 95%.…”
Section: Discussionmentioning
confidence: 99%
“…This study has ascertained cases through the use of a well-established surveillance methodology shown to be more effective than other methods. 16,17 However, it is likely that there is some degree of underascertainment. Previous reports for studies ascertaining cases through the BOSU have indicated that ascertainment rates usually lie between 75 and 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Where compliance is better, it is likely that higher proportions of cases are being identified and reported, which is consistent with comparative trials of surveillance methodologies. 2,3 a Two applications were withdrawn and one study was not accepted as being of insufficient public health importance.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are able to ascertain cases using a well-established methodology shown to be more effective than comparable methods. 2,3 The burden on the ophthalmological community is lessened by removing requests from numerous sources for reporting cases of uncommon disorders. 4 BOSU's supplementary activities include providing advice and assistance to research workers on the design of their studies and increasing awareness within the medical profession of the conditions studied.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the existing notifiable disease surveillance system in the United Kingdom is compared with the system in Sri Lanka. Several evaluation studies to identify the strengths and weaknesses of existing infectious disease surveillance systems (passive and/or active) have been reported (2,3,4,5,6,7,8,9) . However, the literature on comparative studies on disease surveillance systems in two different geographical locations is very limited.…”
Section: Introductionmentioning
confidence: 99%